Structural Delineation and Hydrocarbon Potential Evaluation of Lockhart Limestone in Basal Area, Upper Indus Basin, Pakistan - Shakir, U.; Amjad, M. R.; Mehmood, M. F.; Hussain, M.; Abuzar, M. K.; Ahmad, T.; Aftab, F.; Tahir, A. R. (The Nucleus, 2019)
The Basal area is situated in Upper Indus Basin of Pakistan dominated by intense thrust faulting along with the involvement of salt tectonics, which are responsible for the formation of structural traps in study area. Oil reserves in sedimentary rocks are the source of hydrocarbons for the energy and these reserves are trapped in a structure provided by tectonics. Integration of geological and geophysical tools provide an insight to explore these reserves in the sub surface. Main focus of this research paper is to delineate a suitable structure favorable for hydrocarbon entrapment in the Basal area by integrating seismic and well log data near Fateh Jhang, Attock district, Upper Indus basin, Pakistan. The Upper Indus basin lies in compressional tectonic regime exhibiting thrust faulting with inference of overprints of transpressional strike-slip deformation. Basal oil field lies 77 km south-west of Islamabad with Main Boundary Thrust (MBT) in north, Khairi Murat thrust in south, Jhelum/Soan river in east and Indus river in west. Seismic data interpretation has been performed on given seismic lines by marking faults and reservoir horizons of Chorgali and Lockhart formations using formation tops and making T-D charts via analysis of multiple velocity functions (MVF) of all seismic lines. Mapping of the reservoir formations have confirmed the presence of fault-propagated anticlinal structure in study area. One main fault (throw ~ 100-200 ms) and two back thrust faults EW-oriented with moderate dipping angles have been marked with dips towards North and South respectively. Petrophysical analysis is done on the well Garhi X-01, Gamma Ray, Resistivity and Porosity tracks have confirmed the presence of hydrocarbon in Lockhart Formation of Paleocene age. Three zones have been identified, out of which zone 2 is considered most favorable one due to less shale volume (Vsh), sufficient effective porosity and high hydrocarbon saturation values.